Geographic Information Science 7th International Conference, GIScience 2012, Columbus, OH, USA, September 18-21, 2012. Proceedings - Xiao, Ningchuan; Kwan, Mei-Po.; Goodchild, Michael F.; Shekhar, Shashi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Geographic Information Science, GIScience 2012, held in Columbus, OH, USA in September 2012. The 26 full papers presented were carefully reviewed and selected from 57 submissions. While the traditional research topics are well reflected in the papers, emerging topics that involve new research hot-spots such as cyber infrastructure, big data, web-based computing also occupy a significant portion of the volume.
cyber infrastructure -- big data -- web-based computing.
Keywords: Computer science; Computer software; Database management; Artificial intelligence; Geographical information systems; Computer Science; Database Management; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Geographical Information Systems/Cartography.